STUDENT PERCEPTIONS OF LEARNING VIDEOS IN BASIC NURSING SKILLS COURSES AT THE FACULTY OF HEALTH SCIENCES, AS-SYAFI'IYAH ISLAMIC UNIVERSITY - Fatimah, Siti; Sofiyat, Ali Ilham (Fakultas Sains Dan Teknologi, 2025)
One of the learning outcomes of basic nursing skills courses in the nursing science study, is that after participating in learning, students are expected to be able to: apply the principles and procedures of infection control and patient safety. For this reason, the stidents’ skills students must be perfect so that malpractice does not occur. In overcoming this, it is necessary to develop a video assisted learning model in Basic Nursing Skills Course. This study explored nursing students’ perceptions of using video-assisted in basic nursing skills teaching and learning. This study utilized a descriptive quantitative analysis approach. One hundred and fifty eight (158) nursing students were selected through purposive sampling. The primary data collection method was online questioner survey. Data analysis using descriptive statistics. The results showed that 75% of students use mobile phones in accessing videos for less than 60 minutes, while accessing videos for more than 60 minutes is around 78%, 71% of videos accessed on the youtube platform and 84% of videos accessed on the tiktok platform, 97% of students stated that video-based learning is interesting, as well as student perceptions of the learning model developed will be able to improve student understanding of basic nursing skills courses. It is concluded that student perceptions of the development of video-based learning models are very good and supportive of being applied in basic nursing skills courses.